Mortality and Readmission After Cervical Fracture from a Fall in Older Adults: Comparison with Hip Fracture Using National Medicare Data. Issue 10 (12th October 2015) - Cooper, Zara; Mitchell, Susan L.; Lipsitz, Stuart; Harris, Mitchel B.; Ayanian, John Z.; Bernacki, Rachelle E.; Jha, Ashish K.
<x xml:space="preserve">Abstract</x> Objectives To examine the prevalence of cervical spine fractures after falls in older Americans, to show changes in recent years, and to compare 12‐month outcomes between individuals with cervical and hip fracture after falls. Design Retrospective study of Medicare data from 2007 to 2011. Setting Acute care hospitals. Participants Individuals aged 65 and older with cervical or hip fracture after a fall. Measurements Cervical fracture rate, 12‐month mortality, and readmission rate after injury. Results Rates of cervical fracture increased from 4.6 per 10, 000 in 2007 to 5.3 per 10, 000 in 2011; rates of hip fracture decreased from 77.3 per 10, 000 in 2007 to 63.5 per 10, 000 in 2011. Participants with cervical fracture with and without spinal cord injury (SCI) were more likely than those with hip fracture to receive treatment at large hospitals (59.4% and 54.1% vs 28.1%, P < .001), teaching hospitals (49.3% and 40.0% vs 13.4%, P < .001), and regional trauma centers (46.3% and 38.5% vs 13.0%, P < .001). Participants with cervical fracture without (24.7%) and with SCI (41.7%) had greater risk‐adjusted mortality at 1 year than those with hip fracture (22.7%) (P < .001). By 1 year, 73.4% of participants with cervical fracture with and 59.5% without SCI and 59.3% of those with hip fracture had died or were readmitted to the hospital (P < .001). Conclusion Cervical spinal fractures occur in one of every 2, 000 Medicare beneficiaries annually and appear to be increasing over time. Participants with cervical fracture had greater mortality than those with hip fracture. Given the increasing prevalence and the poor outcomes in this population, hospitals need to develop processes to improve care for these vulnerable individuals.